Should feminists stop talking about culture in the context of violence against Muslim women? The case of “honour killing” - Razack, Sherene (International Journal of Child, Youth and Family Studies, 2021)
The violence, scale, and power of anti-Muslim narratives circulated on the internet and elsewhere continue to have considerable impact on feminist anti-violence initiatives. I examine contemporary responses to “honour killings” with particular reference to the Palestinian, Indian, and North American contexts, reflecting on how anti-violence advocates negotiate the terrain of culture in the case of honour killings. I ask whether the focus on culture has an impact on how courts and society view violence committed by Muslim men (and sometimes women) against Muslim women and girls. I suggest that cultural details contribute little to an enhanced legal understanding of the crime simply because this is not their primary purpose. Instead, the cultural details are part of a pedagogy that conveys a message of the racial and cultural superiority of the dominant society and a corresponding inferiority of Muslim cultures. We should therefore always talk culture with the greatest of restraint lest the racism that accompanies culture talk inhibit our understanding of the violence and limit our capacity to respond to it.